2019
DOI: 10.13189/ujer.2019.070214
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Technostress Levels as an Indicator of Their Psychological Capital Levels

Abstract: The rapid development and easy accessibility of internet and personal computers have increased their use in educational environments as well as in every field. In schools, responsibilities of teachers in using technology have increased within the scope of educational processes and management processes and administrative level, and indirectly it has been determinative in their behavior towards the institution. In this respect, teachers' technostress levels which are the pressure they incur in the use of technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
2
14
0
3
Order By: Relevance
“…Female participants in this study reported higher technostress levels than males. This was also reported by Efilti and Naci Çoklar ( 2019 ) and Thomée et al ( 2012 ) who found that women experience higher levels of anxiety and exhaustion than men in the use of ITC’s. Margetić et al ( 2021 ) found that emotional distress during COVID-19 pandemic was more intensive in women and younger participants.…”
Section: Discussionsupporting
confidence: 80%
“…Female participants in this study reported higher technostress levels than males. This was also reported by Efilti and Naci Çoklar ( 2019 ) and Thomée et al ( 2012 ) who found that women experience higher levels of anxiety and exhaustion than men in the use of ITC’s. Margetić et al ( 2021 ) found that emotional distress during COVID-19 pandemic was more intensive in women and younger participants.…”
Section: Discussionsupporting
confidence: 80%
“…Female participants in this study reported higher technostress levels than males. This was also reported by (E lti & Naci Çoklar, 2019) and (Thomée et al, 2012) who found that women experience higher levels of anxiety and exhaustion than men in the use of ITC's. Liaw's study also indicated that males had more positive perceptions towards computers and Web technologies than females (Liaw, 2002).…”
Section: Discussionsupporting
confidence: 76%
“…Other variables were also related to technostress, such as teaching experience and the level of teachers’ psychological capital. It was thus concluded that technostress is an important predictor of the psychological capital and that a decrease in the technostress level will increase the level of psychological capital [ 81 ].…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%